Effets de l’adaptation Sur la réception du roman français à l'étranger (Journal of the College of Basic Education, 2022)
The novel and cinema became one of the most common types of narrative forms in our modern times. These two new forms not exclude realism, such as: the historical books, diaries, autobiographical books, and travelogues.The scientific progress and the development of the industrial revolution played a major role in developing the cinematic art and made it one of the most remarkable achievements at the end of the nineteenth century.To this day, the cinematic arts attract spectators from different social classes, while the theatrical arts become exclusive to those who belong to high social ranks, well educated, and wealthy.Any creative work whether it is a novel or play, a painting or sculpture seeks to convey a moral message. The cinematic director, on the other hand, tries to reflect his beliefs and opinions as a reader to the novel, and then he tries to achieve fame and appreciation from the spectators who watch his mastery of film making.The films that is based on the novels and its effect on the reader/spectator is the basic aim that the research tries to show. It also presents a wide range of critical opinions, ideas, and arguments about the work.